Environmental factors shaping copepod distributions in cave waters of the Lessinian unsaturated karst (NE-Italy) - Vaccarelli, Ilaria; Cerasoli, Francesco; Mammola, Stefano; Fiasca, Barbara; Di Cicco, Mattia; Di Lorenzo, Tiziana; Stoch, Fabio; Galassi, Diana Maria Paola (Frontiers in Ecology and Evolution, 2023)
The unsaturated karst represents a transitional zone connecting the land surface to the water table of the underlying saturated zone through percolating water and small perched aquifers. It constitutes a significant groundwater reservoir and hosts a high biodiversity of specialized and endemic species. Whereas investigating this ecotone can shed light on the invertebrate diversity of the whole karst system, ecological studies in the unsaturated karst have been hampered by access, mapping, and sampling challenges. We studied the unsaturated zone of 52 caves in the Lessinian Massif (NE-Italy), which is dominated by carbonate rocks interspersed with spot areas composed mainly of igneous rocks. Our aim was to understand which ecological and historical factors may have shaped the distribution of the groundwater crustacean copepods at a regional spatial scale in the Lessinian unsaturated karst. We collected 33 species belonging to the orders Harpacticoida and Cyclopoida. Species richness estimators and related species accumulation curves suggest an exhaustive sampling effort. A hydrologic analysis performed in a Geographic Information System environment divided the study area in three distinct drainage basins: Eastern Lessini, Lessinian Core, and Western Lessini. Regression analyses indicated that richness of non-stygobitic copepods (i.e. surface-water species which exploit groundwater for different purposes) was mainly driven by inter-basin differences. Richness of stygobitic copepods (i.e. obligate groundwater dwellers) was instead strongly related to lithological features and responded negatively to surface thermal variability. Next, we used a kernel density estimation to spatially explore diversity patterns in the area. The highest density of stygobitic harpacticoids was identified in the Eastern Lessinian basin, which is lithologically more heterogeneous and surrounded by practically non-aquiferous igneous rocks that may limit dispersal. Conversely, the Western Lessinian basin hosted a high density of stygobitic cyclopoid species. This spatial pattern suggests different colonization pathways for the two taxa, with a strong effect of igneous rocks in hampering dispersal of most harpacticoids. Lithological barriers seemingly did not affect non-stygobitic copepods, which were found across the whole area. Altogether, these results emphasize the key role played by the interaction of hydrological features, climate, and lithology in determining different copepod biodiversity patterns in the unsaturated karst.